Regional Taxes and Levies Contribution to the Increase of Regional Original Income - Rusli Rusli (Journal of Social Commerce, 2022)
This study aims to determine how to determine the contribution of regional taxes and levies to the increase in local revenue at the Regional Revenue Agency of Mamuju Regency. The type of research used in this research is descriptive qualitative. The analytical technique used in this research is to conduct field studies and literature studies. Based on the results of data analysis that has been carried out, it can be concluded that the contribution of local tax revenues has increased in 2013-2014 while in 2015-2017 experienced fluctuating symptoms in each type of tax. Then the contribution of regional levies changes which fluctuate every year in the period 2013-2017. As well as local tax revenues and regional levies contribute to increasing the original revenue of the Mamuju Regency.